The iron distribution and magnetic properties of schistosome eggshells: implications for improved diagnostics. - Stephan Karl; Lucía Gutiérrez; Rafael Lucyk-Maurer; Roland Kerr; Renata R F Candido; Shu Q Toh; Martin Saunders; Jeremy A Shaw; Alexandra Suvorova; Andreas Hofmann; Michael J House; Robert C Woodward; et al. (Public Library of Science (PLoS), 2013)
BACKGROUND: Schistosoma mansoni and Schistosoma japonicum are the most frequent causative agents of human intestinal schistosomiasis. Approximately 200 million people in the world are infected with schistosomes. Diagnosis of schistosomiasis is often difficult. High percentages of low level infections are missed in routine fecal smear analysis and current diagnostic methodologies are inadequate to monitor the progress of parasite control, especially in areas with low transmission. Improved diagnostic methods are urgently needed to evaluate the success of elimination programs. Recently, a magnetic fractionation method for isolation of parasite eggs from feces was described, which uses magnetic microspheres to form parasite egg - magnetic microsphere conjugates. This approach enables screening of larger sample volumes and thus increased diagnostic sensitivity. The mechanism of formation of the conjugates remains unexplained and may either be related to specific surface characteristics of eggs and microspheres or to their magnetic properties. METHODS/PRINCIPAL FINDINGS: Here, we investigated iron localization in parasite eggs, specifically in the eggshells. We determined the magnetic properties of the eggs, studied the motion of eggs and egg-microsphere conjugates in magnetic fields and determined species specific affinity of parasite eggs to magnetic microspheres. Our study shows that iron is predominantly localized in pores in the eggshell. Parasite eggs showed distinct paramagnetic behaviour but they did not move in a magnetic field. Magnetic microspheres spontaneously bound to parasite eggs without the presence of a magnetic field. S. japonicum eggs had a significantly higher affinity to bind microspheres than S. mansoni eggs. CONCLUSIONS/SIGNIFICANCE: Our results suggest that the interaction of magnetic microspheres and parasite eggs is unlikely to be magnetic in origin. Instead, the filamentous surface of the eggshells may be important in facilitating the binding. Modification of microsphere surface properties may therefore be a way to optimize magnetic fractionation of parasite eggs.